The Developmental Transcriptome of Bagworm, Metisa plana (Lepidoptera: Psychidae) and Insights into Chitin Biosynthesis Genes - Rahmat, Nur Lina (Genes (Basel), 2020)
Bagworm, Metisa plana (Lepidoptera: Psychidae) is a ubiquitous insect pest in the oil palm plantations. M. plana infestation could reduce the oil palm productivity by 40% if it remains untreated over two consecutive years. Despite the urgency to tackle this issue, the genome and transcriptome of M. plana have not yet been fully elucidated. Here, we report a comprehensive transcriptome dataset from four different developmental stages of M. plana, comprising of egg, third instar larva, pupa and female adult. The de novo transcriptome assembly of the raw data had produced a total of 193,686 transcripts, which were then annotated against UniProt, NCBI non-redundant (NR) database, Gene Ontology, Cluster of Orthologous Group, and Kyoto Encyclopedia of Genes and Genomes databases. From this, 46,534 transcripts were annotated and mapped to 146 known metabolic or signalling KEGG pathways. The paper further identified 41 differentially expressed transcripts encoding seven genes in the chitin biosynthesis pathways, and their expressions across each developmental stage were further analysed. The genetic diversity of M. plana was profiled whereby there were 21,516 microsatellite sequences and 379,895 SNPs loci found in the transcriptome of M. plana. These datasets add valuable transcriptomic resources for further study of developmental gene expression, transcriptional regulations and functional gene activities involved in the development of M. plana. Identification of regulatory genes in the chitin biosynthesis pathway may also help in developing an RNAi-mediated pest control management by targeting certain pathways, and functional studies of the genes in M. plana.